(3GdEjVGM hGdJcedIs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG Ydi CKQ Pdc CWGd Gddg HbGA Gdedc YVO GdOhdI aEfj LeYJ aj gPG GdcJGH CHhGHkG ef GdYQHjI s
(3BNQgG (B:s
(3gPG HGH eG jdRe ajg EHOGd GdjGA ef GdhGh GdJj gj dGe s
(3fSNI SGOSI JJab aj ChdgG eY Chd GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG JbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B49 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B211s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs